2020
DOI: 10.1186/s40623-020-01270-7
|View full text |Cite
|
Sign up to set email alerts
|

On data reduction methods for volcanic tremor characterization: the 2012 eruption of Copahue volcano, Southern Andes

Abstract: Improving the ability to detect and characterize long-duration volcanic tremor is crucial to understand the long-term dynamics and unrest of volcanic systems. We have applied data reduction methods (permutation entropy and polarization degree, among others) to characterize the seismic wave field near Copahue volcano (Southern Andes) between June 2012 and January 2013, when phreatomagmatic episodes occurred. During the selected period, a total of 52 long-duration events with energy above the background occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
(46 reference statements)
1
11
0
Order By: Relevance
“…S1-S5). These results support those of previous case studies (Glynn and Konstantinou 2016;Melchor et al 2020;Konstantinou et al 2022) and suggest that PE is potentially useful and can be easily incorporated into existing volcano monitoring schemes. The conclusions of this work are summarized as follows:…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…S1-S5). These results support those of previous case studies (Glynn and Konstantinou 2016;Melchor et al 2020;Konstantinou et al 2022) and suggest that PE is potentially useful and can be easily incorporated into existing volcano monitoring schemes. The conclusions of this work are summarized as follows:…”
Section: Discussionsupporting
confidence: 89%
“…In this work we use seismic noise in order to calculate Permutation Entropy (hereafter referred to as PE) and reconstruct its temporal variation prior to and during the three eruption cycles at Shinmoedake. PE is a metric that quantifies the degree of randomness in a time series and its application to other volcanoes previously (see Glynn and Konstantinou 2016;Melchor et al 2020) has shown promise in recognizing precursory changes prior to eruptions. First, we begin with a description of the seismic network around Shinmoedake, the data availability, and with a general introduction to the methodology we used.…”
Section: Introductionmentioning
confidence: 99%
“…Previous volcano‐seismic studies (Glynn & Konstantinou, 2016; Melchor et al., 2020) used only the vertical component of seismic data to calculate PE. We compared PE using the vertical and both horizontal components (Figure S2 in Supporting Information S1) of the stations S1, S2, S3, S4, and S5.…”
Section: Seismic Preprocessing and Pe Setting At Strokkurmentioning
confidence: 99%
“…The one is stable over the whole period, while the other occurs as swarms that mark the onset of phreatic activity. Melchor et al (2020) analyzed volcanic tremors during the 2012 and 2013 phreatic eruptions at Copahue volcano, southern Andes. They could discriminate the tremor signals from the noise by the lower permutation entropies and higher degrees of polarizations even if the signal-to-noise level is low.…”
Section: Papers On Similar Volcanoes In Japan and The Worldmentioning
confidence: 99%